Transcriptome Analysis of Gerbera hybrida Including in silico Confirmation of Defense Genes Found - Fu, Yiqian; Esselink, G. Danny; Visser, Richard G. F.; van Tuyl, Jaap M.; Arens, Paul (Frontiers in Plant Science, 2016)
For the ornamental crop Gerbera hybrida, breeding at the moment is done using conventional methods. As this has drawbacks in breeding speed and efficiency, especially for complex traits like disease resistance, we set out to develop genomic resources. The leaf and flower bud transcriptomes of four parents, used to generate two gerbera populations, were sequenced using Illumina paired-end sequencing. In total, 36,770 contigs with an average length of 1397 bp were generated and these have been the starting point for SNP identification and annotation. The consensus contig sequences were used to map reads of individual parents, to identify genotype specific SNPs, and to assess the presence of common SNPs between genotypes. Comparison with the non-redundant protein database (nr) showed that 29,146 contigs gave BLAST hits. Of sequences with blast results, 73.3% obtained a clear gene ontology (GO) annotation. EST contigs coding for enzymes were found in Kyoto Encyclopedia of Genes and Genomes maps (KEGG). Through these annotated data and KEGG molecular interaction network, transcripts associated with the phenylpropanoid metabolism, other secondary metabolite biosynthesis pathways, phytohormone biosynthesis and signal transduction were analysed in more detail. Identifying genes involved in these processes could provide genetic and genomic resources for studying the mechanism of disease resistance in gerbera.